Deep-water zooplankton in the Mediterranean Sea: Results from a continuous, synchronous sampling over different regions using sediment traps. (August 2017) - Danovaro, R.; Carugati, L.; Boldrin, A.; Calafat, A.; Canals, M.; Fabres, J.; Finlay, K.; Heussner, S.; Miserocchi, S.; Sanchez-Vidal, A.
Abstract: Information on the dynamics of deep-sea biota is extremely scant particularly for long-term time series on deep-sea zooplankton. Here, we present the results of a deep-sea zooplankton investigation over one annual cycle based on samples from sediment trap moorings in three sub-basins along the Mediterranean Sea. Deep-sea zooplankton assemblages were dominated by copepods, as in shallow waters, only in the Adriatic Sea (>60% of total abundance), but not in the deep Ionian Sea, where ostracods represented >80%, neither in the deep Alboran Sea, where polychaetes were >70%. We found that deep-sea zooplankton assemblages: i) are subjected to changes in their abundance and structure over time, ii) are characterized by different dominant taxa in different basins, and iii) display clear taxonomic segregation between shallow and near-bottom waters. Zooplankton biodiversity decreases with increasing water depth, but the equitability increases. We suggest here that variations of zooplankton abundance and assemblage structure are likely influenced by the trophic condition characterizing the basins. Our findings provide new insights on this largely unknown component of the deep ocean, and suggest that changes in the export of organic matter from the photic zone, such as those expected as a consequence of global change, can significantly influence zooplankton assemblages in the largest biome on Earth. Highlights: One-year variability of deep-sea Mediterranean zooplankton by using sediment trap. Zooplankton abundance and taxonomic composition varied significantly over time. Clear taxonomic segregation between near-surface and near-bottom waters. The downward fluxes of OC and TN influence zooplankton abundance and biodiversity.